The Strategy of Islamic Religious Education Teacher in Developing Students' Spiritual Intelligence (SQ) at Wiworotomo Vocational School Purwokerto - Rahma, Putri; Sutarman (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Introduction to The Problem: In the modern era, students must develop strong spiritual intelligence to navigate life's complexities and maintain emotional balance. Purpose: This research aims to: (1) examine the role of Islamic Religious Education (IRE) teachers in fostering spiritual intelligence at SMK Wiworotomo Purwokerto; (2) identify factors supporting or inhibiting this development; and (3) assess the outcomes of teachers' efforts in enhancing students' spiritual intelligence. Design/methods/approach: A qualitative research methodology with a field-based approach was employed. Primary data were collected from the principal, the vice principal, three IRE teachers, and five students. Secondary data were obtained from magazines, newspapers, and other relevant documents. Data collection methods included observation, interviews, and document analysis, while qualitative data analysis was used. Triangulation ensured validity and reliability. Findings: The findings reveal that IRE teachers at SMK Wiworotomo Purwokerto foster spiritual intelligence through collective prayers, greetings between teachers and students, and regular congregational prayers at the mosque. Activities like Dhuha prayers, Friday sermons, and charitable fundraising also contribute to spiritual development. Communal fasting during Ramadan strengthens spiritual bonds and enhances students' spiritual intelligence. Research implications/limitations: This study highlights the importance of religious activities in shaping students' spiritual intelligence and promoting mental and emotional resilience. Educational institutions could incorporate such practices into curricula to support holistic student development. The research also identifies factors affecting the effectiveness of IRE teaching efforts, providing insights for improvement. Additionally, spiritual development enhances teacher-student relationships, fostering a positive school environment. Originality/value: Future research could explore the broader applicability of these findings across diverse educational contexts..